THE POWER OF MASS MEDIA IN BUSINESS - Egamberdieva Shokhsanam; Yuldasheva F.F. (Journal of new century innovations, 2022)
Annotation: This article provides information about the power of mass media and its platforms in business. The contribution of social networks to success in the field of business and the importance of online marketing are discussed.